PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI YANG TERCATAT DI BURSA EFEK INDONESIA - Andi Sumarlin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This goal is to know : (I) To know Fundamental Factor That is Return On Total Assets (ROA), Earning Per Share (EPS), Book Value (BV) and Debt to Equity Ratio (DER) effect simultioneously to the Share Price at the Pharmacentical Company Listed on the Indonesia Stock exchange ; (2) to know Return On Assets (ROA), Earning Per Share (EPS), Book Value (BV) and Debt to Equity Ratio (DER), dominant Influence on stock prices in the Pharmacentical Industry Companies Listed in Indonesia Stock Exchange. Population were observed in this Study is the Pharmacentical Companies Listed in Stock Exchange Indonesian of 2008-2012. The coice of the manufacturing industry is defined as a Sample for the industry at most listing on the stock Exchange Indonesia. Sample selection is done by using purposive sampling method. The result showed that Return On Total Assets (ROA), Earning Per Share (EPS), Book Value (BV) and Debt to Equity Ratio (DER) effect simultioneously to the stock price on the company is Pharmacentical industry Listed in Indonesia Stock Exchange. From the Result showed Return on Total Assets (ROA) the most dominant influences on the stock Prices in the Pharmacentical industry Company listed in Indonesia Stock Exchange.